Literature Study Of The Effect Of Registration Services On Outpatient Satisfaction In Hospitals - Farah Tifanny Aisyah Anindya Putri; Nurdina (Journal of Hospital Management and Services, 2019)
The factor of patient satisfaction with health services greatly influences the number of visits. The first gate for patients who will use hospital services is the registration section, especially for outpatients. Because you have to immediately fill out several forms to complete the medical record file, unlike inpatient treatment where you still have time to fill in the forms. Patients often complain of dissatisfaction at the registration department because the service takes a long time and the patient does not understand the flow. This research uses a literature review method, namely a synthesis of systematic, clear, comprehensive literature studies, by identifying, analyzing, evaluating through collecting existing data with an explicit search method and involving a critical review process in selecting studies. The data used were 10 journals obtained from the screening results of a number of journals from the Mendeley journal portal, Google Scholar, and PubMed. In 10 journals, 90% or 9 journals used questionnaires as data collection instruments, while 10% or 1 journal used qualitative analysis methods with interviews. On average, the questionnaire used is on a Likert scale and records the length of service time in the registration section for outpatients. It can be concluded from this journal review that outpatient satisfaction with registration services can be influenced by service waiting times. Even though they have to wait a long time, outpatients can feel satisfied with the friendly service provided by the staff and the good facilities and infrastructure at the hospital.